Respuesta :
Answer:
- [tex] a = - 8.617 \frac{m}{s^2} [/tex]
- [tex] a = - 0.8798 \ g [/tex]
- [tex]Tb = 6.64 \ s [/tex]
- [tex]\frac{Tb}{Tr} = 16.6[/tex]
Explanation:
a and b
We can use the following formula, from kinematics:
[tex](v_f)^2-(v_i)^2 = 2 \ a \ d[/tex]
where [tex]v_f[/tex] is the final speed, [tex]v_i[/tex] is the initial speed, a is the acceleration and d the distance traveled.
Knowing that the final speed is zero, and the initial speed is
[tex]v_i = 206 \frac{km}{h} = 206 \frac{km}{h} \frac{1000 \ m}{1 \ km} \frac{1 \ h}{3600 \ s} = 57.22 \frac{m}{s}[/tex]
we obtain
[tex](0)^2-(57.22 \frac{m}{s})^2 = 2 \ a \ 190 \ m[/tex]
[tex] a = \frac{ - \ 3,274.13 \frac{m^2}{s^2} }{ 2 \ 190 \ m} [/tex]
[tex] a = - 8.617 \frac{m}{s^2} [/tex]
Now, knowing that
[tex] g = 9.806 \frac{m}{s^2} [/tex]
then
[tex] a = \frac{- 8.617 \frac{m}{s^2}} { 9.806 \frac{m}{s^2} } \ g [/tex]
[tex] a = - 0.8798 \ g [/tex]
c
We can use the following formula
[tex]v(t) = v_0 + a t[/tex]
so
[tex]0 = 57.22 \frac{m}{s} - 8.617 \frac{m}{s^2} \ Tb[/tex]
[tex]Tb = \frac{ 57.22 \frac{m}{s} }{ 8.617 \frac{m}{s^2} } [/tex]
[tex]Tb = 6.64 \ s [/tex]
d
[tex]\frac{Tb}{Tr} = \frac{ 6.64 \ s }{ 0.4 s }[/tex]
[tex]\frac{Tb}{Tr} = 16.6[/tex]